Fresh insights on the nexus between green foreign financing and efficient use of natural resources: The moderating role of institutional quality - Yen, Nguyen Hong (International Journal of Innovative Research and Scientific Studies, 2025)
It is more probable that both industrialized and developing nations have a great deal of potential for putting sustainable logistics into practice, but they are also severely disrupted by climate change. The goal of this article is to establish a link between Green Foreign Direct Investment (FDI) and Natural Rents through the use of a worldwide database. In order to quantify natural rents, five different measures are used, including those for coal, minerals, natural gas, forests, and aggregates. We find that the expansion of Green FDI contributes to the growth of natural rents as a result of the empirical findings of our investigation. To elucidate the correlation between Green Foreign Direct Investment and Natural Rents, various indicators such as economic growth (INC), trading activities as a percentage of GDP (EXP), industrialization level (IND), net foreign direct investment (FDI), government effectiveness (GE), ISO 14001 certificates (EI_ISO), and environmental performance index (EPI) are considered. To enhance the accuracy of the model, variables related to institutional quality are also taken into account. Based on our research, we believe the long-term impact of Green FDI will be stronger, particularly in nations with an advanced stage of growth. Within the framework of the analysis, the robustness and reliability of the findings are maintained regardless of heterogeneity, fixed effects, and endogeneity.